Histomorphometry of the Ligaments Using a Generic-Purpose Image Processing Software, a New Strategy for Semi-Automatized Measurements. - Ballesteros, Rafael; Bonsfills, Nuria; Chacón, Marta; García-Lázaro, Javier; Gómez-Barrena, Enrique (Journal of Digital Imaging, 2012)
Gold chloride technique can be combined with Adobe Photoshop® software to yield a quantitative assessment of the different areas in heterogeneous structures as are ligament. A semi-automatized method based on the sum of two- and three-dimensional morphological criteria upon colorimetric criteria allows the identification and measurement of the area occupied by a structure of interest. It also allows the quantification of color intensity to differentiate structures with similar staining avidity, like vessels and nerves. This computer-assisted, semiquantitative procedure for computerized morphometry is relatively simple to perform. The accuracy, efficiency, and reproducibility of this method based on a commercially available imaging program were considered adequate when tested on the anterior cruciate ligament of the cat. Image normalization by trained observers using a commercially available software package designed for photography, applied to a sample randomly chosen, has provided the means of making reproducible measurements of heterogeneous structures.